Controlling the dynamics of cavity magnon polariton via microwave polarization - Lihua Zhong; Chao Zhang; B. M. Yao (AIP Advances, 2022)
Cavity magnon polaritons (CMPs) are quasiparticles that combine the advantages of high-speed photons and long-lived spins. The coupling between magnons and photons can be tuned to chiral situations by controlling the microwave polarization, which is important to manipulate the asymmetrical energy flow for coherent signal processing. Here, by strongly coupling a magnon mode to the microwave field with controllable polarization from a cross cavity, we realize the flexible control of CMP dynamics via the chiral coupling effect. Such control allows the cavity resonance to evolve into doublet or triplet spectra under zero-detuning condition depending on the left- and right-handed circular or linear polarization at the center of our cross cavity via the phase control technique. In addition to the experimental findings, we establish a harmonic oscillator model that can well describe our results. Furthermore, we display a functionality of nonreciprocal transmission using the chiral condition in coupling. Directional transmission is observed for all CMP triplet modes, exhibiting a significant chiral contrast in both dispersion and amplitude. Our results demonstrate that CMPs built in a cross cavity can realize tunability from microwave polarization and can function as an on-chip device with a one-way energy transfer, which has potential applications in switches, isolators, and logical gates that utilize CMP dynamics.